Methodology of Conducting Physics Laboratory and Practical Courses to Students of Technical Higher Education Institutions - Ismailov Davron Makhmadalievich (Peerian Journals Publishing, 2022)
Higher Education Institution is aimed at forming a system of scientific knowledge, skills and their use in future engineers, which allows students not only to apply the acquired knowledge in practice, but also to acquire scientific methods of scientific knowledge, for example, experiment, practical or laboratory, independently acquire new knowledge, process and allows storage
Keywords: engineers, laboratory